Pengaruh Program Pertukaran Mahasiswa Merdeka (PMM) dan Kampus Mengajar terhadap Motivasi Belajar Mahasiswa Jurusan Ekonomi Universitas Negeri Medan - Cantika Elizabeth Sigalingging; Lenti Susanna Saragih (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This research is motivated by the low learning motivation of students despite participating in MBKM programs such as Merdeka Student Exchange (PMM) and Kampus Mengajar. This phenomenon is seen from the fact that there are still students who are not diligent in studying, do not show strong interest in their field of study, and are not yet encouraged to complete lecture assignments well. This becomes an important reason for researchers to examine further whether there is an influence from these two programs on students' learning motivation. The purpose of this study is to determine and analyze the influence of PMM and Kampus Mengajar Programs on the learning motivation of Economics Department students, Universitas Negeri Medan. This research uses a quantitative approach by distributing questionnaires through a Likert scale questionnaire. The number of respondents was 52 students selected through purposive sampling technique, namely students who had participated in one or both programs. The results showed that both partially and simultaneously, the PMM and Kampus Mengajar Programs had a significant influence on students' learning motivation. The t-test showed that PMM had a significance value of 0.042 and Kampus Mengajar had 0.002, both below 0.05. The F-test simultaneously showed a significance value of 0.001. The multiple regression equation obtained was Y = 29.047 + 0.145X₁ + 0.184X₂, and the coefficient of determination (R²) was 0.552, meaning that 55.2% of the learning motivation variable is explained by PMM and Kampus Mengajar. Based on these findings, it can be concluded that student involvement in the PMM and Kampus Mengajar Programs has an influence on increasing the learning motivation of Economics Department students, Universitas Negeri Medan. Thus, participation in both programs becomes one of the important factors contributing to students' internal drive in undertaking the educational process.